A scoping review of low-intensity cognitive behavioral therapy studies across Asia - Cameron Shi Ern Tan; Keane Kang Xiang Ong; Laura Sophie Arden-Gardner; Fiqri Nur Haziq Abu Bakar; Sin Yee Lim; Amalia Ariffin; Jonathan Han Loong Kuek (SSM - Mental Health, 2025)
Introduction: Mental health conditions are increasing globally, yet access to mental health services remains limited, particularly in Asia. Low-intensity cognitive behavioral therapy (LI-CBT) interventions offer a scalable, cost-effective approach to addressing mild-to-moderate mental health issues. However, the implementation of LI-CBT in Asia remains unclear. This scoping review examines existing research on LI-CBT in Asia, identifies research gaps, and explores the extent of cultural adaptations made to these interventions, providing an overview of the literature and highlighting future research and practice avenues. Methods: Adopting the PRISMA-ScR guidelines, a systematic search was conducted in PubMed, PsycINFO, CINAHL, EMBASE, Web of Science, and Scopus, focusing on peer-reviewed studies published between 2005 and 2024. Primary research studies conducted in Asia that employed LI-CBT interventions according to a formal framework for classifying these programs were included. Data were charted and analyzed to identify key themes in various study characteristics, intervention types, outcomes, and cultural adaptations. Results: A total of 42 studies from 12 Asian countries were identified, with Japan and China contributing the most research. Most studies reported positive outcomes; research gaps remain due to the heterogeneity of implementation, small sample sizes, inadequate controls, short follow-up periods, and inconsistent cultural adaptations beyond language translation. Conclusion: LI-CBT holds promise for improving mental health accessibility in Asia. However, further research is needed to enhance cultural adaptation considerations and create standardized intervention frameworks that can be modified for use in diverse populations.